Response to a Critic of A Declaration and Constitution for a Free Society - Brian P. Simpson (Research Synergy Foundation, 2022)
This article is in response to Scott Douglas Gerber’s review of my book A Declaration and Constitution for a Free Society in the fall 2021 issue of American Political Thought. It addresses issues raised by Gerber regarding my argument for lowering the eligibility age of the president of the United States in the U.S. Constitution. It also addresses Gerber’s claims about my proposal to eliminate the Commerce Clause in the U.S. Constitution. In addition, I discuss his review of my recommendation to change the tax system. Finally, I analyze his review of my changes to the United States Declaration of Independence. The response shows that Gerber’s review was not a serious or honest attempt to review the book. The response will help the reader not only better understand the contents of the book, but it will also help the reader understand the nature of individual rights and freedom.